2006
DOI: 10.1210/jc.2006-0736
|View full text |Cite
|
Sign up to set email alerts
|

Insulin Sensitivity in Patients with Primary Aldosteronism: A Follow-Up Study

Abstract: Insulin resistance is present in patients with tumoral and idiopathic aldosteronism, but the defect appears less severe than in patients with essential hypertension. Treatment with surgery or aldosterone antagonists restores rapidly and persistently normal sensitivity to insulin.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
193
4
4

Year Published

2009
2009
2024
2024

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 231 publications
(217 citation statements)
references
References 30 publications
9
193
4
4
Order By: Relevance
“…Our finding that aldosterone's association with glucose metabolism is independent of PRA is consistent with observations made in the pathological state of primary aldosteronism, which is associated with higher levels of insulin resistance 3. The treatment of primary aldosteronism with adrenalectomy or mineralocorticoid receptor antagonism improves insulin sensitivity and insulin secretion 27, 28. The largest pharmacologic diabetes mellitus prevention trials examining RAAS antagonism as a primary end point, the DREAM (Diabetes Reduction Assessment with Ramipril and Rosiglitazone Medication) study and the NAVIGATOR (Nateglinide and Valsartan in Impaired Glucose Tolerance Outcome Research) study, both showed modest reductions in risk of diabetes mellitus with an ACE‐I or ARB, which were significant in NAVIGATOR (14% risk reduction; P <0.0001) 29, 30.…”
Section: Discussionsupporting
confidence: 90%
“…Our finding that aldosterone's association with glucose metabolism is independent of PRA is consistent with observations made in the pathological state of primary aldosteronism, which is associated with higher levels of insulin resistance 3. The treatment of primary aldosteronism with adrenalectomy or mineralocorticoid receptor antagonism improves insulin sensitivity and insulin secretion 27, 28. The largest pharmacologic diabetes mellitus prevention trials examining RAAS antagonism as a primary end point, the DREAM (Diabetes Reduction Assessment with Ramipril and Rosiglitazone Medication) study and the NAVIGATOR (Nateglinide and Valsartan in Impaired Glucose Tolerance Outcome Research) study, both showed modest reductions in risk of diabetes mellitus with an ACE‐I or ARB, which were significant in NAVIGATOR (14% risk reduction; P <0.0001) 29, 30.…”
Section: Discussionsupporting
confidence: 90%
“…31 In our study, there were no significant differences in the prevalence of diabetes mellitus, higher plasma glucose levels or use of antidiabetic drugs among all studied groups.…”
Section: Discussioncontrasting
confidence: 47%
“…We found that treatment with MRAs decreased VAT but not SAT in patients with PA; however, serum lipids and HOMA-IR were not influenced by the medical treatment. Catena et al [31] reported that treatment with surgery or MR antagonists rapidly and persistently restores normal sensitivity to insulin in patients with PA, which was independent of plasma potassium levels. In their report, HOMA-IR was decreased at 6 months after treatment and increased to the baseline levels over an average period of 5.7 years.…”
Section: Discussionmentioning
confidence: 99%
“…Patients with PA have a significantly higher prevalence of metabolic syndrome than those with essential hypertension (EHT) [10,11,12]. The mineralocorticoid receptor (MR) is expressed in the kidneys and in adipose tissue.…”
Section: Introductionmentioning
confidence: 99%